Physics

Newton's Law of Universal Gravitation Calculator


\( F \)

= \( G \enspace \displaystyle{ \frac{ m_1 \enspace m_2 }{ r^2 } } \)

 

= \( G \enspace \times \enspace \)
\( \mathrm{ kg } \enspace \times \enspace \) \( \mathrm{ kg } \)
\( ( \) \( \mathrm{ m } \) \( ) \) \( \mathrm{^2} \)

 

=   \( \mathrm{ N } \, (\mathrm{ newtons }) \)

=   \( \mathrm{ N } \, (\mathrm{ newtons }) \)   (to significant figures)


\( m_1 \)

= \( \displaystyle{ \frac{ F \enspace r^2 }{ G \enspace m_2 } } \)

 

=
\( \mathrm{ N } \enspace \times \enspace \) \( ( \) \( \mathrm{ m } \) \( ) \) \( \mathrm{^2} \)
\( G \enspace \times \enspace \) \( \mathrm{ kg } \)

 

=   \( \mathrm{ kg } \)

=   \( \mathrm{ kg } \)   (to significant figures)


\( m_2 \)

= \( \displaystyle{ \frac{ F \enspace r^2 }{ G \enspace m_1 } } \)

 

=
\( \mathrm{ N } \enspace \times \enspace \) \( ( \) \( \mathrm{ m } \) \( ) \) \( \mathrm{^2} \)
\( G \enspace \times \enspace \) \( \mathrm{ kg } \)

 

=   \( \mathrm{ kg } \)

=   \( \mathrm{ kg } \)   (to significant figures)


\( r \)

= \( \displaystyle{ \sqrt{ \frac{ G \enspace m_1 \enspace m_2 }{ F } } } \)

 

=
\( ( \)
\( G \, \times \, \) \( \mathrm{ kg } \)\( \, \times \, \) \( \mathrm{ kg } \)
\( \mathrm{ N } \)
\( ) \)
\(^{-2}\)

 

=   \( \mathrm{ m } \)

=   \( \mathrm{ m } \)   (to significant figures)